PEMBERIAN HAK DALAM PEMANFAATAN TANAH PESISIR PANTAI UNTUK TRANSMIGRASI RING I DI KABUPATEN KULON PROGO - Erna Sri Wibawanti; Francisca Romana Harjiyatni (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2008)
The research concludes that the type of land rights given to transmigrant is not accordance with the provisions in the Act no. 15 of 1997 on Transmigration. According to this Act, the type of land for transmigration is an ownership right. Meanwhile, the type of lands on Ring I Transmigration is right to utilize the land. This is because the land is owned by Paku Alam (Paku Alam Grond/Paku AlamGround). The Staffs at Pakualaman will issue a licensing letter to the tranmigrants for using the lands. The lands in original place of transmigrants is still owned by them. Apart from difficulties faced by transmigrants, most respondents are satisfied with the Ring I Transmigration . However, they hope the local government can provide them a stronger type of land right, the owner right. They also hope that the government can establish more facilities in the transmigration areas , such as road, electricity and agriculture equipments.